Kandungan Nutrien Nitrat dan Fosfat Pada Air di Kawasan Estuari DAM, Badung, Bali - Manik, Melani Indah Sari; Perwira, Ima Yudha; Ernawati, Ni Made (Journal of Marine and Aquatic Sciences; Vol 9 No 2 (2023), 2024)
Nitrate and phosphate nutrients are important nutrients in waters, but in conditions that exceed the limit will cause problems for the aquatic environment. One of the aquatic environments that has the potential to experience increased nitrate and phosphate content is the DAM Estuary located in Badung, Bali. This study aims to determine the current condition of nitrate and phosphate content in water in the DAM Estuary. Water sampling was carried out at 4 different station. Station 1 represents the inlet of the DAM Estuary, Station 2 and 3 represent the middle part of the DAM Estuary, while Station 4 represents the outlet of the DAM Estuary. Nitrate was measured using Hanna HI 713 Reagent, while Phosphate was measured using Salifert Nitrate KIT Reagent. In addition, temperature, pH, TDS and DO measurements were also carried out in water. The results showed that the nitrate and phosphate content in the water in the DAM Estuary was still below the water quality standard for all classes according to Government Regulation no. 82 of 2001 concerning Water Quality Management and Water Pollution Control. Other water quality parameters also show good conditions in accordance with these regulations.